Pengembangan Bahan Pembelajaran Berbasis Hypercontent pada Pembelajaran Tematik Daerah Tempat Tinggalku - Herlina Herlina (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2019)
Advances in information technology have an impact on the variety of learning materials used in schools. This condition must be responded to by developing learning materials that are compatible with technological developments, especially technology based on handheld devices such as phones and tablets. This study aims to produce hypercontent-based learning materials in elementary schools on the theme of the district where I live. The method used is development research with the Rowntree model. The results showed that based on expert validation hypercontent-based learning materials were valid and effectively used in learning. Thus hypercontent-based learning materials can be used for learning in elementary schools